MORPHOLOGICAL AND MOTOR PREREQUISITES OF DIFFERENTIATED PHYSICAL EDUCATION OF SCHOOLCHILDREN - Holovanova, I.A.; Arefyev, V.G.; Masenko, L.V.; Masol, V.V.; Salamakha, O.Ye.; Popov, M.D.; Lyakhova, N.A. (World of Medicine and Biology, 2025)
The effort to improve the quality of teaching physical education at school should be based on taking into account the gender-age characteristics of the morphological and physical condition of the student youth. The purpose of the study was to substantiate the prerequisites for differentiated physical education of learners with different rates of physical development in physical education lessons. The study involved 1,192 girls aged 8–17 who studied in schools in Kyiv (Ukraine). The choice of schoolgirls is due to the fact that over 30 % of them already in elementary school have health problems. Materials and methods: pedagogical testing of physical abilities, anthropometry, physiological tests, sample statistical method. Results: It was found that in schoolgirls aged 8–17 with different rates of physical development, present statistically significant differences in the levels of manifestation of physical abilities and it observed in 41 % of cases. Such differences are most clearly visible during puberty (from 11 to 15 years old). The presence of these differences indicates the need for a differentiated approach in selecting means and methods of physical education, taking into account not only chronological age but also the pace (level) of physical development of schoolgirls.
Keywords: physical education; girls 8–17 years old; pace of physical development; health